Socialization of Sacrificial Animal Slaughter in accordance with Islamic Sharia - Bastoni; Fitri Dian Perwitasari; Retno Widyani; Devi Yuliananda (Ann Publisher, 2024)
The purpose of community service activities is to know the Islamic law on qurban, choose good sacrificial animals, take care of sacrificial animals according to sharia, and maintain sacrificial meat that is SAHUT (Healthy, Safe, Halal, Intact, and Thoyiban). The results of the resume material presented on how to slaughter sacrificial animals by Islamic law and public health of the Animal Husbandry Study Program: 1. Read thamid sentences; 2. A sharp knife is used for slaughter on the ventral part of the neck approximately 8-10 cm behind the arch of the lower jaw so that it is cut at once the trachea, jugular vein - arteria communis, and esophagus. Ante mortem (physical examination of animals before slaughter) and post-mortem (examination of carcasses, meat, and offal of animals that have been slaughtered). Both of these checks are carried out before being distributed to the public. The examination process is carried out by a medical officer or veterinary paramedic under the supervision of an authorized veterinarian. The questions asked showed the enthusiasm of the participants. The recommendation of participants is that this activity involves hands-on practice rather than just the delivery of material.